VISUALIZING SUNDANESE IDENTITY THROUGH ANGKLUNG-INSPIRED APP ICON UI DESIGN - Tiara, Tiara Amelia Rahmawati; Irfan Hendrian; Rizki Maulana Rachman (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2025)
Sundanese culture possesses a wealth of traditional values and symbols that can be visualized through various digital media, one of which is mobile application icons. This study aims to design angklung-themed application icons as an effort to visualize Sundanese culture in the context of user interface (UI) design. Using a qualitative approach, the design process was carried out through three main stages: collecting visual references, creating manual sketches, and digitizing the designs. The main visual elements of the angklung, such as vertical and horizontal bamboo tubes, were creatively adapted into common application icons including Home, Contact, Message, Settings, Files, Browser, Music, Camera, Phone, and Clock. The results indicate that these icon designs not only fulfill aesthetic and functional aspects of modern UI but also successfully represent local cultural values visually. These findings reinforce the idea that digital interfaces can serve as effective and adaptive media for cultural representation in the technological era. UI design based on local culture such as this is expected to strengthen Indonesia's visual identity within the digital ecosystem.